Experimental study on grouting diffusion and reinforcement law of grouting backfilling mining in caving zone - Zhihua Li; Enlong Zou; Ke Yang; Qian Geng; Guojun Ma; Jiawei Qi; Zhi Yang (Scientific Reports)
Abstract Grouting in caving zones is complex and difficult to visualize, especially regarding the filling space, slurry flow, and bearing capacity of the gangue-slurry mixture. To address these challenges, experiments were conducted to investigate the flow characteristics of fly ash slurry and confined compression tests under various gangue particle grading schemes. The findings show the following: (1) The calculated and measured porosities are similar, providing an initial method for assessing the filling space. The slurry injection volume is proportional to the gangue porosity, but high slurry concentrations or tightly packed particles may cause grouting infiltration. (2) The stress–strain curves of both the gangue bulk and gangue-slurry mixture follow an exponential relationship. Maximum strain values are influenced by porosity and the proportion of larger particles. (3) Internal energy changes show distinct temporal patterns, with more pronounced fluctuations occurring in the medium-term, indicating greater internal structural adjustments during this phase. (4) Creep tests indicate that the mixture exhibits gradual axial strain changes, suggesting better stability and bearing capacity.